PENGARUH PENGETAHUAN PERPAJAKAN, TINGKAT PENDIDIKAN DAN KESADARAN TERHADAP KEPATUHAN WAJIB PAJAK (STUDI KASUS PADA KPP MALANG UTARA) - Wanda Bela Listy; Noor Shodiq Askandar; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to determine the effect of tax knowledge, education level, and awareness on taxpayer compliance. The researcher determined that individual taxpayers who are active and registered at the North Malang Pratama Tax Office are the population. Meanwhile, the researcher used the slovin formula in determining the sample with 99 taxpayers as respondents. The research method used is primary data quantitative research with questionnaire data collection techniques using a 5-point Likert scale. The data analysis method used is multiple linear regression analysis using SPSS tools. The results of this study indicate that Tax Knowledge, Education Level and Awareness have a simultaneous effect on Taxpayer Compliance. Partially, knowledge of taxation has a positive effect on taxpayer compliance, education level has no effect on taxpayer compliance, and awareness has a negative effect on taxpayer compliance.Keywords : Tax Knowledge, Education Level, Taxpayer Awareness and Compliance